Synergizing Electromedical and Biomedical Engineering for Health Technology Self-Reliance in Indonesia - I Wayan Sadwika (Jurnal Indonesia Sosial Sains, 2026)
Indonesia's envision to become a high-income, self-reliant nation in technology by 2045, as articulated in the Indonesia Emas 2045 vision, depends heavily on a resilient and innovative health technology ecosystem (Sadwika, 2026). Two similar but frequently conflated professions underpin this ecosystem: Electromedical Engineering (Teknik Elektromedik), a vocational discipline regulated under Kepmenkes No. 371/2007 and represented by the Ikatan Ahli Teknik Elektromedik Indonesia (IKATEMI), and Biomedical Engineering (BME), an academic-research discipline oriented toward medical technology innovation and represented by the Konsorsium Ilmu Biomedical Engineering Indonesia (KIBI). Employing a narrative policy-analysis approach, this article synthesizes regulatory documents, institutional reports, and peer-reviewed studies published between 2007 and 2024, selected for their direct relevance to electromedical and biomedical engineering regulation, education, and workforce conditions in Indonesia. Evidence was thematically coded and triangulated across regulatory, academic, and institutional sources to clarify professional boundaries, competencies, and regulatory status, and to examine the persistent role confusion, workforce shortages, and fragmented governance hindering Indonesia's medical technology sector. We argue that Electromedical Engineering constitutes the operational basis of clinical safety and equipment reliability, while Biomedical Engineering drives domestic innovation, import substitution, and policy advocacy. Rather than competing jurisdictions, these professions represent complementary links in a single value chain, from device conception to bedside maintenance. Guided by this synthesis, the article proposes an integrated strategic agenda spanning regulatory harmonization, curriculum strengthening, research funding expansion, and international collaboration, concluding that deliberate synergy between these two professions is indispensable to achieving Indonesia's health technology sovereignty by 2045.